Quaternary onset and evolution of Kimberley coral reefs (Northwest Australia) revealed by high-resolution seismic imaging - Bufarale, Giada; Collins, L.; O'Leary, Mick; Stevens, Alexandra; Kordi, M.; Solihuddin, T. (Elsevier Ltd, 2016)
© 2016 Elsevier Ltd.The inner shelf Kimberley Bioregion of Northwest Australia is characterised by a macrotidal setting where prolific coral reefs growth as developed around a complex drowned landscape and is considered a biodiversity "hotspot". High-resolution shallow seismic studies were conducted across various reef settings in the Kimberley (Buccaneer Archipelago, north of Dampier Peninsula, latitude: between 16°40'S and 16°00'S) to evaluate stratigraphic evolution, interaction with different substrates, morphological patterns and distribution. Reef sites were chosen to assess most of the reef types present, particularly high intertidal planar reefs and fringing reefs. Reef internal acoustic reflectors were identified according to their shape, stratigraphic position and characteristics. Two main seismic horizons were identified marking the boundaries between Holocene reef (Marine Isotope Stage 1, MIS 1, last 12 ky), commonly 10-20 m thick, and MIS 5 (Last Interglacial, LIG, ~120 ky, up to 12 m thick) and Proterozoic rock foundation over which Quaternary reef growth occurred. Within the Holocene Reef unit, at least three minor internal reflectors, generally discontinuous, subparallel to the reef flat were recognised and interpreted as either growth hiatuses or a change of the coral framework or sediment matrix. The LIG reefs represent a new northernmost occurrence along the Western Australian coast. The research presented here achieved the first regional geophysical study of the Kimberley reefs. Subbottom profiles demonstrated that the surveyed reefs are characterised by a multi-stage reef buildup, indicating that coral growth occurred in the Kimberley during previous sea level highstands. The data show also that antecedent substrate and regional subsidence have contributed, too, in determining the amount of accommodation available for reef growth and controlling the morphology of the successive reef building stages. Moreover, the study showed that in spite of macrotidal conditions, high-turbidity and frequent high-energy cyclonic events, corals have exhibited prolific reef growth during the Holocene developing significant reef accretionary structures. As a result coral reefs have generating habitat complexity and species diversity in what is a biodiversity hotspot.